1991
DOI: 10.1007/bf01311229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cisapride on chronic idiopathic constipation in children

Abstract: The efficacy of cisapride, a new prokinetic drug, as a treatment for chronic functional constipation of childhood was studied in 20 constipated children. Each subject had a stool frequency less than 4/week and/or total gastrointestinal transit time greater than 33 hr and was randomly assigned to double-blind treatment with either cisapride (N = 10) or placebo (N = 10) for 12 weeks. Stool habits, total gastrointestinal transit time, and anorectal motility were evaluated in all children before and at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 15 publications
0
37
1
Order By: Relevance
“…24 In contrast R093877 had no specific effect on rectal distension thresholds or anorectal electrosensory thresholds, despite showing a significant effect on increasing bowel frequency. Results from this study indicate that R093877 has no obvious effect on sensory or sphincter function.…”
Section: Discussionmentioning
confidence: 90%
“…24 In contrast R093877 had no specific effect on rectal distension thresholds or anorectal electrosensory thresholds, despite showing a significant effect on increasing bowel frequency. Results from this study indicate that R093877 has no obvious effect on sensory or sphincter function.…”
Section: Discussionmentioning
confidence: 90%
“…In children it increases lower oesophageal sphincter pressure,6 enhances gastric emptying,7-9 and increases intestinal transit time 1011 It has been widely used in children for a variety of conditions including gastro-oesophageal reflux,6 12 13 intestinal pseudo-obstruction,14 15 and constipation 16 17. It is well tolerated by most children 2…”
Section: Discussionmentioning
confidence: 99%
“…Later, four randomized, controlled studies tested the efficacy of cisapride in children with constipation [7•,28-30]. Initially, Staiano et al [29] showed, in 20 children randomized either to cisparide, 0.2 mg/kg three times daily, or placebo, for a 12-week period, that cisapride significantly increased stool frequency, and decreased laxative use and transit time. Later, Odeka et al [30] randomized 37 children either to cisparide, 0.2 mg/kg three times daily, or to placebo, for an 8-week period, and no significant differences were shown.…”
Section: Cisapridementioning
confidence: 97%